Utilizing Imaging Analysis to Determine the Internal Structure Characteristics of Asphalt Mixtures for Permeability and Moisture Damage Performance - Nithinan Hemnithi; Preeda Chaturabong (Coatings, 2023)
Moisture is a significant problem in standard pavements, causing asphalt mixtures to deteriorate due to insufficient water permeability. This failure from moisture damage is often caused by precipitation accumulation or poor drainage, which allows water to weaken adhesion by seeping between the aggregates and the asphalt. The relationship between permeability and aggregate contact length is believed to be inverse. To effectively assess water permeability performance and moisture damage, an asphalt concrete design criterion was established using the Image Processing and Analysis System (IPAS) to determine aggregate contact lengths. The objective of this research was to use laboratory experiments in conjunction with IPAS to investigate air-void-controlled asphalt mixtures with various material properties and assess the correlation of water permeability with other factors. The results show that AC60/70, AC60/70+Carbon Black, and AC60/70+SBS combinations with coconut peat filler had the lowest permeability coefficient (k) among similar mixtures, with values of 0.056 × 10−5 cm/s, 0.010 × 10−5 cm/s, and 1.508 × 10−5 cm/s, respectively. Both the dense and porous gradations of the modified asphalt binder demonstrated positive linear relationships between TSR and permeability. This study found a strong linear relationship between TSR (tensile strength ratio) and k (permeability coefficient) in both dense and porous modified asphalt binder gradations, with R2 values of 0.79 and 0.74, respectively. Additionally, we found that the number of contact points and contact length in the skeleton strongly influenced the mixes’ permeability, with a linear trend of 0.93 for both indices.
Keywords: Asphalt Pavement Performance Evaluation; Infrastructure Maintenance and Monitoring; Geophysical Methods and Applications